Increased levels of citrullinated antithrombin in plasma of patients with rheumatoid arthritis and colorectal adenocarcinoma determined by a newly developed ELISA using a specific monoclonal antibody - Ordóñez, Adriana; Yélamos, Jose; Pedersen, Shona; Miñano, Antonia; Conesa-Zamora, Pablo; Kristensen, Soren R.; Stender, Mogens T.; Thorlacius-Ussing, Ole; Martínez-Martínez, Irene; Vicente, Vicente; Corral, Javier (Thrombosis and Haemostasis, 2010)
Citrullination is a post-translational modification that plays essential roles in both physiological processes and disease. Recent studies have found increased levels of citrullinated antithrombin in patients with rheumatoid arthritis and in different malignant tumours. Antithrombin, the main haemostatic serpin, loses its anticoagulant function via citrullination, which might contribute to the pathogenesis or thrombotic side effects of these disorders. We have developed a specific monoclonal antibody against citrullinated antithrombin. We determined the levels of citrullinated antithrombin and anti-FXa activity in plasma from 66 donors, 17 patients with rheumatoid arthritis and 77 patients with colorectal adenocarcinoma (42 suffering from venous thrombosis). Healthy subjects had negligible amounts of citrullinated antithrombin in plasma (7.9 ± 22.1 ng/ml), while it significantly increased in patients with rheumatoid arthritis or adenocarcinoma (159.7 ± 237.6 ng/ml and 36.8 ± 66.1 ng/ml), levels that, however, did not modify the plasma anticoagulant activity. Moreover, we did not find association between citrullinated antithrombin and the thrombotic risk in patients with adenocarcinoma. In conclusion, we have developed an antibody specific for citrullinated antithrombin that allows its quantification in biological samples, offering a new tool for the analysis of citrullination in different diseases. We confirm increased levels of citrullinated antithrombin in plasma of patients with rheumatoid arthritis and adenocarcinoma. This modification, probably local, could have pathological consequences in both disorders, but only affects a minor fraction of plasma antithrombin, resulting in no significant reduction of global anticoagulant activity. This result explains the absence of association of this marker with an increased risk of thrombosis in patients with colorectal adenocarcinoma.
Keywords: Antithrombin; citrullination; monoclonal antibody; rheumatoid arthritis; cancer